Arrangement and method for supporting shell into breech-loading weapon barrell - KOIVULA ESA; NIEMI PEKKA (2011)
The invention relates to an arrangement for supporting a shell (1) into a barrel (2) of a breech-loading weapon, the arrangement comprising a rim-flanged support element (6) attachable to a shell tail (4). The arrangement is characterized in that the arrangement comprises a propelling charge element (12) comprising a propelling charge (14) and a primer (13), the element having a threading (15a) suited for the shell tail allowing the support element (6) to be fastened to the shell tail by threading the propelling charge element (6) into the tail of the shell (1) through the support element (6). The invention further relates to a method of supporting a shell into a barrel of a breech-loading weapon.